Test and Analysis of Vibration Signal of an Automotive Transmission System - Meng Fanlong; Ma Weijin; Zhang Jiping; Wang Junyuan; Chen Jianwei; Zhang Zhengpeng (Jixie chuandong)
In order to understand the vibration of an automotive transmission system,taking the type automotive transmission as the research object,the vibration signal tests and analysis of the automotive transmission under multi- conditions are carried out,and a greater contribution to vibration frequencies of the transmission are obtained. Comparing the vibration frequency with the modal test results of the transmission,the frequency which is easy to cause the resonance of the transmission is confirmed. The results can lay a foundation for taking measures to avoid the resonance frequency,to reduce the vibration and the optimized design of vehicle structure.